Myelin imaging in amyotrophic and primary lateral sclerosis. Issue 7 (December 2013) - Kolind, Shannon; Sharma, Rakesh; Knight, Steven; Johansen-Berg, Heidi; Talbot, Kevin; Turner, Martin R.
Abstract: Primary lateral sclerosis (PLS) has been regarded as a rare, extreme form of amyotrophic lateral sclerosis (ALS). Like ALS, it is a clinical diagnosis without established biomarkers. We sought to explore loss of cerebral myelin in relation to clinical features, including cognitive impairment, in cases of both ALS and PLS. A novel MRI sequence (mcDESPOT) sensitive to water pools within myelin and intra- and extra-cellular spaces was applied to 23 ALS patients, seven PLS patients and 12 healthy controls, with interval follow-up in 15 ALS and four PLS patients. Results demonstrated that PLS patients were distinguished by widespread cerebral myelin water fraction reductions, independent of disease duration and clinical upper motor neuron burden. ALS patients showed a significant increase in intra- and extra-cellular water, indirectly linked to neuroinflammatory activity. Limited measures of cognitive impairment in the ALS group were associated with myelin changes within the anterior corpus callosum and frontal lobe projections. Longitudinal changes were only significant in the PLS group. In conclusion, in this exploratory study, myelin imaging has potential to distinguish PLS from ALS, and may have value as a marker of extramotor involvement. PLS may be a more active cerebral pathological process than its rate of clinical deterioration suggests.